Diagnosis of sepsis with inflammatory biomarkers, cytokines, endothelial functional markers from SIRS patients. Issue 7 (18th February 2022) - Xue, Mingming; Xu, Feixiang; Yang, Yilin; Tao, Zhengang; Chen, Yumei; Wang, Sheng; Yin, Jun; Min, Min; Shi, Dongwei; Yao, Chenling; Song, Zhenju
Abstract: Background: Sepsis is a life-threatening illness with a challenging diagnosis. Rapid detection is the key to successful treatment of sepsis. To investigate diagnostic value, the plasma protein profiles of inflammatory biomarkers, cytokines, and endothelial functional markers were compared between healthy controls, SIRS, and septic patients. Methods: The plasma protein profiles were performed by Luminex Assay in a cohort of 50 SIRS patients, 82 septic patients and 25 healthy controls. Fourteen plasma proteins were analyzed in the same cohort: IL-1β, IL-6, IL-8, IL-10, CCL-2, VEGF, VEGF-C, VEGFR2, CD62E, CD62P, MFG-E8, ICAM-1, TFPI, Urokinase. Result: IL-2R, IL-6, IL-8, IL-10, CCL-2, ICAM-1, and Urokinase were significantly higher in sepsis patients than SIRS patients. VEGF, IL-1β, CD62E, CD62P, MFG-E8, and TFPI have no statistical difference. VEGF-C, VEGFR2 were significantly different in SIRS patients than sepsis patients. Urokinase, ICAM-1, and VEGFR2 were significantly different between sepsis group and SIRS group. The AUCs of Urokinase, ICAM-1, and VEGFR2 and the combination for the diagnosis of sepsis were 0.650, 0.688, 0.643, and 0.741, respectively. Conclusions: Most patients have the higher level of several cytokines and developed endothelial cell injury in the initial phase of sepsis, Urokinase, ICAM-1, and VEGFR2 may be useful to evaluate severity and prognosis of sepsis patients.